Sprue-Like Enteropathy and Liver Injury: A Rare Emerging Association with Olmesartan - Mihir Odak MD; Ndausung Udongwo MD; Nasam Alfraji MD; Min Zheng MD, PhD; Saddam Zaidi MD (SAGE Publishing, 2021)
Olmesartan-induced enteropathy is an underreported phenomenon, first described in 2012. While olmesartan's antihypertensive properties were confirmed early on, its association with a sprue-like enteropathy was subsequently noted. Although this association has been reported with olmesartan, there have been few reports of this association with other angiotensin-receptor blockers. We present a case of a 79-year-old male who presented with diarrhea, weight loss, jaundice, and transaminitis. Further history revealed that he had been taking olmesartan 40 mg daily for hypertension. Workup of his diarrhea and jaundice included duodenal and liver biopsies revealed findings consistent with a sprue-like enteropathy and an autoimmune hepatitis-like pattern. On discontinuation of olmesartan, his 1-month follow-up revealed significant improvement in his clinical status as well as his liver function tests. Olmesartan is an effective antihypertensive medication; however, physicians must be mindful of its side effect of causing a sprue-like enteropathy and liver injury. Patients should be counseled on discontinuing olmesartan, and they should be started on an alternative therapy for hypertension.